Initial investigation on binding agents for compact powder formulation from rice (bedak sejuk) - Sim, Siew Ping; Noorhisham Tan Kofli (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bedak sejuk is a type of traditional cosmetic product that is favoured by women that possesses potential to be marketed as cosmetic product in the form of loose powder or compact powder. At present, there is no research available on the bedak sejuk in the compact format. Therefore, the main objective of this study is to produce a compact powder by introducing several binding agents. The soaking process of rice grain in the water was carried out for 84 days (14 days soaking interval, 6 times soaking water changed) to produce the paste of bedak sejuk. It was then dried and crushed using mortar and pestle before being sieved to be characterizes (particles sizes and bonds- FTIR). The compact format of bedak sejuk were prepared by addition of different binding agents namely ethanol, isopropyl alcohol, polyvinyl alcohol(PVA), magnesium stearate and jojoba oil to evaluate its cracking level, hardness through drop test and easiness of application onto the skin. Based on the result, the particle size of uncrushed and crushed bedak sejuk were at 1000-2000μm and ranging 150-250 μm respectively. The FTIR analysis showed that the functional groups existed in bedak sejuk were OH bond, C-H bond, C=O bond, C-O-H bond and C-O bond. Each type of compact bedak sejuk produced from each binding agent exhibits their own strengths and weaknesses respectively. In short, alcohol (PVA) is found to be the best binding agent used due to its easiness to be applied onto the skin.